The path toward the abyss: the dissolution of the old social pact, the emergence of new technologies, and the challenges for progressive policies - Giovanni Dosi (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2025)
There are at least three existential challenges to contemporary societies, as we know them, namely, first, the complete rupture of the social pact, which characterized Glorious Decades after WWII in most of Western societies; and second, the deepening of the patterns of informatization and 'intelligent' automation with the associated modifications in labor relations and mechanisms of social control. All that, third, is coupled with a climate crisis that might have well reached a tipping point toward a global ecological disaster. The end of the social pact went together with the ubiquitous diffusion of a neoliberal ideology, which poisoned all the domains of social and political life. This paper discusses such existential challenges, together with some urgent policy way outs.
Keywords: A14; P16; O30; Z13; Z18; 330; Social democratic pact; Income and power distributions; Social conflict; AI-based technologies; Neoliberalism; Green New Deal